Predictive value of the resistance of the probe to pass through the lesion in the diagnosis of peripheral pulmonary lesions using radial probe endobronchial ultrasound with a guide sheath - Hu, Zhenli; Tian, Sen; Wang, Xiangqi; Wang, Qin; Gao, Li; Shi, Yuxuan; Li, Xiang; Tang, Yilian; Zhang, Wei; Dong, Yuchao; Bai, Chong; Huang, Haidong (Frontiers in Oncology, 2023)
Background Transbronchial lung biopsy guided by radial probe endobronchial ultrasonography with a guide sheath (EBUS-GS-TBLB) is becoming a significant approach for diagnosing peripheral pulmonary lesions (PPLs). We aimed to explore the clinical value of the resistance of the probe to pass through the lesion in the diagnosis of PPLs when performing EBUS-GS-TBLB, and to determine the optimum number of EBUS-GS-TBLB. Methods We performed a prospective, single-center study of 126 consecutive patients who underwent EBUS-GS-TBLB for solid and positive-bronchus-sign PPLs where the probe was located within the lesion from September 2019 to May 2022. The classification of probe resistance for each lesion was carried out by two bronchoscopists independently, and the final result depended on the bronchoscopist responsible for the procedures. The primary endpoint was the diagnostic yield according with the resistance pattern. The secondary endpoints were the optimum number of EBUS-GS-TBLB and factors affecting diagnostic yield. Procedural complications were also recorded. Results The total diagnostic yield of EBUS-GS-TBLB was 77.8%, including 83.8% malignant and 67.4% benign diseases (P=0.033). Probe resistance type II displayed the highest diagnostic yield (87.5%), followed by type III (81.0%) and type I (61.1%). A significant difference between the diagnostic yield of malignant and benign diseases was detected in type II (P = 0.008), whereas others did not. Although most of the malignant PPLs with a definitive diagnosis using EBUS-GS-TBLB in type II or type III could be diagnosed in the first biopsy, the fourth biopsy contributed the most sufficient biopsy samples. In contrast, considerably limited tissue specimens could be obtained for each biopsy in type I. The inter-observer agreement of the two blinded bronchoscopists for the classification of probe resistance was excellent (κ = 0.84). Conclusion The probe resistance is a useful predictive factor for successful EBUS-GS-TBLB diagnosis of solid and positive-bronchus-sign PPLs where the probe was located within the lesion. Four serial biopsies are appropriate for both probe resistance type II and type III, and additional diagnostic procedures are needed for type I.